A longitudinal transcriptomic analysis of Rhipicephalus microplus midgut upon feeding - Stephen Lu; Jéssica Waldman; Luís Fernando Parizi; Itabajara da Silva Vaz Junior; Lucas Tirloni (Ticks and Tick-Borne Diseases, 2024)
Rhipicephalus microplus, a highly host-specific tick that primarily feeds on cattle, posing a significant threat to livestock production. The investigation of tick physiology is crucial for identifying potential targets in tick control. Of particular interest adult female ticks undergo a significant expansion of the midgut during feeding, leading to an over 100-fold increase in body weight. Beyond the functions of storing and digesting blood meals, the tick midgut plays a crucial role in acquiring and transmitting pathogens. However, our understanding of tick midgut physiology remains limited. In this study we conducted a comprehensive longitudinal transcriptome analysis of the midgut from adult female R. microplus ticks collected at various feeding stages, providing an overview of the transcriptional modulation in this organ as feeding progress. By employing a de novo assembly approach followed by coding-sequences (CDS) extraction, 60,599 potential CDS were identified. In preparation for functional annotation and differential expression analysis, transcripts that showed an average transcript per million (TPM) ≥ 3 in at least one of the biological conditions were extracted. This selection process resulted in a total of 10,994 CDS, which were categorized into 24 functional classes. Notably, our differential expression analysis revealed three main transcriptional profiles. In the first one, representing the slow-feeding stage, the most abundant functional classes were the “protein synthesis” and “secreted” groups, reflecting the highly active state of the tick midgut. The second profile partially accounts for the rapid-feeding stage, in which a high number of differentially expressed transcripts was observed. Lastly, the third transcriptional profile represents post-detached ticks. Notably the highest number of modulated transcripts was observed up to 48 h post-detachment (hpd), however no major differences was observed up to 168 hpd. Overall, the data presented here offers a temporal insight into tick midgut physiology, contributing to the identification of potential targets for the development of anti-tick control strategies.